1767. Structured Treatment Interruptions in HIV-Infected Patients Receiving Antiretroviral Therapy—Implications for Future HIV Cure Trials: A Systematic Review and Meta-analysis. (26th November 2018) - Stecher, Melanie; Löhnert, Annika Y; Klein, Florian; Lehmann, Clara; Wyen, Christoph; Fätkenheuer, Gerd; Vehreschild, Janne
Abstract: Background: Safety and tolerability of analytical treatment interruption (TI) as part of HIV cure studies has been discussed controversially. In this systematic review and meta-analysis, we report current evidence for the occurrence of adverse effects during different types of TI. Methods: A systematic literature search on studies reporting on TIs was conducted using a defined search term, covering the period from January 1988 to May 2017. All interventional and observational studies were reviewed, and results were extracted based on predefined criteria. We evaluated the proportion of adverse effects during TI by using a random effect meta-analysis model. A meta-regression model was calculated to explore the variation across studies and the influence of key factors. Results: We identified 1, 048 studies, of which we obtained data from 24 studies investigating TI including 7, 961 individuals. Sample sizes varied from 6 to 5, 472 subjects. The number of reported events during TI ranged from 0 to 241. Follow-up intervals during TI varied from 2 days up to 3 months. We compared reported adverse effects in studies with long TI (>4 weeks) by the lengths of follow-up intervals, comparing narrow (≤4 weeks) and wide (>4 weeks) follow-up during TI. The proportion of patients exhibiting adverse events during long TI was 1% (95% CI 0–4, I 2 = 24.9%) in studies with narrow and 10% (95% CI 5–117, I 2 = 95.1%) in studies with wide follow-up intervals, with an overall reported rate of 5% (95% CI: 3–15, z = 3.93, P ≤ 0.00) (Figure 1). The number of reported deaths was relatively low, but higher in studies with wide follow-up compared with studies with narrow follow-up (Figure 2). Meta regression analysis indicated that adverse events were increasing with the length of the monitoring interval (β = 0.75, 95% CI 0.24–1.27, P = 0.007) (Figure 3). Conclusion: Current evidence indicates that studies with narrow follow-up intervals did not show a substantial increase of adverse effects other than viral rebound during TI. Analytical treatment interruption may be a safe strategy as part of HIV cure trials if patients undergo intense follow-up routines. Disclosures: All authors: No reported disclosures.